Sustainable healthcare practices: Pathways to a carbon-neutral future for the medical industry - David Bamidele Olawade; Tunbosun Theophilus Popoola; Eghosasere Egbon; Aanuoluwapo Clement David-Olawade (Sustainable Futures)
The healthcare sector is essential for public health but contributes substantially to environmental pollution and carbon emissions, largely through energy-intensive operations, extensive waste generation, and resource-heavy pharmaceutical production. As climate change intensifies, there is a growing imperative for healthcare to adopt carbon-neutral practices that align with global sustainability goals. This narrative review explores the pathways through which healthcare can transition toward carbon neutrality, focusing on energy-efficient hospital designs, eco-friendly medical supplies, sustainable waste management, and low-carbon pharmaceutical manufacturing. Energy-efficient hospital design utilizes renewable energy, sustainable architecture, and AI-driven energy optimization to lower operational emissions. Environmentally sustainable medical supplies reduce single-use plastics by incorporating biodegradable and reusable materials, as well as sustainable procurement practices. Waste management strategies, including waste segregation, recycling, and energy recovery systems, help reduce healthcare’s environmental footprint, while green chemistry and renewable energy integration in pharmaceutical manufacturing further mitigate emissions. Although financial, regulatory, and operational challenges remain, advances in green technology and increasing awareness provide new opportunities for healthcare organizations to adopt sustainable practices. By prioritizing both environmental responsibility and patient care, the healthcare sector can contribute significantly to global climate objectives. This review highlights the importance of collaboration, policy support, and investment in sustainable healthcare to ensure a resilient, low-carbon future.